Genetic analysis of cis-enhancers associated with bone mineral density and periodontitis in the gene SOST - Avneesh Chopra; Jiahui Song; January Weiner 3rd; Dieter Beule; Arne S. Schaefer (PLoS ONE, 2025)
A haplotype block at the sclerostin (SOST) gene correlates with bone mineral density (BMD) and increased periodontitis risk in smokers. Investigating the putative causal variants within this block, our study aimed to elucidate the impact of linked enhancer elements on gene expression and to evaluate their role in transcription factor (TF) binding. Using CRISPR/dCas9 activation (CRISPRa) screening in SaOS-2 cells, we quantified disease-related enhancer activities regulating SOST expression. Additionally, in SaOS-2 cells, we investigated the influence of the candidate TFs CCAAT/enhancer-binding protein beta (CEBPB) on gene expression by antisense (GapmeR) knockdown, followed by RNA sequencing. The periodontitis-linked SNP rs9783823 displayed a significant cis-activating effect (25-fold change in SOST expression), with the C-allele containing a CEBPB binding motif (position weight matrix (PWM) =  0.98, Pcorrected =  7.7 x 10-7). CEBPB knockdown induced genome-wide upregulation but decreased epithelial-mesenchymal transition genes (P =  0.71, AUC =  2.2 x 10-11). This study identifies a robust SOST cis-activating element linked to BMD and periodontitis, carrying CEBPB binding sites, and highlights CEBPB’s impact on epithelial-mesenchymal transition.